Boosting Austria's Innovation Performance - Leibfritz, Willi (OECD Economics Department Working Papers, 2007)
Enhancing growth through more innovation has become a priority for Austrian policy makers in line with European policies as laid down in the Lisbon Agenda. This paper discusses Austria's innovation performance, its innovation policies, and general framework conditions for innovation and growth. Austria has increased its R&D spending as a share of GDP over the last ten years, largely reflecting more business R&D, and aims at increasing it further to 3% of GDP by 2010. Innovation activity as measured by output indicators has also improved in various fields, including the number of innovating SMEs. Furthermore, policy instruments and institutions have been improved and a culture of policy evaluation is developing. However, the paper identifies some weaknesses, particularly in general economic framework conditions, which may limit the creation and diffusion of innovation and productivity growth. It suggests focusing more on these framework conditions, notably by strengthening competition in non-manufacturing product markets, such as retail and professional services, reducing the cost of firm creation and improving human capital. It also argues that focusing on a numerical target for R&D spending as an end in itself is very unlikely to be cost effective. With its university reform in 2002, Austria has made a major step in improving the efficiency of tertiary education but more needs to be done